A visible light photocatalytic composite material and preparation method thereof

By combining magnetic Fe3O4 with TiO2/g-C3N4 photocatalytic shell, using heterojunction and surface functionalization technology, the efficiency and stability problems of existing photocatalytic materials in the treatment of complex pollutants are solved, and the efficient and circulating multi-pollutant treatment effect is achieved.

CN119549182BActive Publication Date: 2025-05-02EASTERN GANSU UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510113246.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-05-02
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

When existing photocatalytic materials deal with complex pollutants, the treatment efficiency of multiple pollutants and the long-term stability of catalysts are weak. At the same time, the separation and recycling of powdered photocatalysts limit their large-scale promotion and application.

Method used

The magnetic Fe3O4 is organically combined with the photocatalytic shell (TiO2/g-C3N4), and the photogenerated electron-hole separation efficiency is significantly improved by using heterojunction, and the efficient adsorption and reduction of organic components and heavy metal ions in wastewater can be achieved through surface functionalization.

Benefits of technology

The photocatalytic materials with wide spectrum response, high selective removal ability, strong stability and recyclable use are achieved, solving the shortcomings of traditional photocatalytic materials in complex pollution systems, and simplifying the recycling and reuse of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549182B_ABST
    Figure CN119549182B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of photocatalytic materials, and particularly relates to a visible-light photocatalytic composite material and a preparation method thereof. Among them, the visible-light photocatalytic composite material comprises the following raw materials by weight: 10-50 g of magnetic nanocores, 20-80 g of TiO2 precursors, 20-80 g of stabilizers, 40-100 g of g-C3N4 precursors, and 50-200 g of modifiers. Based on the high-efficiency photocatalytic performance and magnetic separation function, the separation efficiency of photo-generated electrons and holes is improved through a heterojunction, and magnetic Fe3O4 and TiO2 / g-C3N4 are organically combined to play a role in degrading organic pollutants. At the same time, specific adsorption and reduction of heavy metal ions are realized through surface functionalization modification, so as to solve the problems of narrow visible-light response range, difficult recovery of catalysts, and poor heavy metal selective removal effect in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalytic materials, and in particular relates to a visible light photocatalytic composite material and a preparation method thereof. Background Art

[0002] With the acceleration of the process of social industrialization, heavy metal pollution in water has become a core issue of concern in the environmental field. Cr, which is highly toxic, difficult to degrade and bioaccumulate, 3+ , Pb 2+ Heavy metal ions such as ions seriously threaten ecosystems and human health. At present, traditional sewage treatment methods such as chemical precipitation, adsorption and ion exchange have limitations in operating costs, selectivity and treatment efficiency, and are increasingly unable to meet the needs of complex pollution systems. Photocatalytic technology has become an ideal choice for treating sewage containing heavy metals due to its low energy consumption, green environmental protection and high efficiency in degrading a variety of pollutants. Although many studies have significantly improved the visible light utilization efficiency and heavy metal removal ability of photocatalysts through methods such as band gap regulation, surface functional modification and heterogeneous structure construction, they are still relatively weak in terms of treatment efficiency for multiple pollutants in complex pollution systems and long-term stability of catalysts. In addition, the separation and recovery of powdered photocatalysts after sewage treatment also limits their large-scale promotion and application.

[0003] Therefore, the development of new photocatalytic materials with wide spectral response, highly selective removal ability, strong stability and recyclability is a key direction to promote the practical engineering application of photocatalytic technology. Summary of the invention

[0004] In view of the above situation, the present invention provides a visible light photocatalytic composite material and a preparation method thereof, wherein the magnetic Fe 3 O 4 With photocatalytic shell (TiO 2 / gC 3 N 4 ) are organically combined, based on efficient photocatalytic performance and magnetic separation function, the heterojunction is used to significantly improve the photogenerated electron-hole separation efficiency; through surface functionalization, efficient adsorption and reduction of organic components and specific heavy metal ions in sewage are achieved, the raw materials used have strong chemical stability, and the prepared photocatalytic composite materials can be recycled many times, which solves the problems of narrow visible light response range, difficult catalyst recovery and poor heavy metal selective removal effect in the prior art.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0006] The present invention provides a visible light photocatalytic composite material, which comprises the following raw materials by weight: 10-50 g of magnetic nanocore, TiO 2Precursor 20-80 g, stabilizer 20-80 g, gC 3 N 4 Precursor 40-100 g and modifier 50-200 g.

[0007] Furthermore, the magnetic nanocore comprises the following raw materials by weight: FeCl 3 6H 2 O 27-54 g, FeSO 4 7H 2 O 20-40 g and 25% (v / v, volume fraction) NH 4 OH solution 50-100 g.

[0008] Furthermore, the TiO 2 The precursor is selected from Ti(OBu) 4 (tetrabutyl titanate), Ti(OiPr) 4 (tetraisopropyl titanate) and LiTiO 3 Any one of (lithium titanate).

[0009] Furthermore, the stabilizer is selected from any one of acetic acid, acetylacetone, ethyl acetate and triethanolamine.

[0010] Furthermore, the gC 3 N 4 The precursor is selected from any one of urea, dicyandiamide, thiourea and citrulline.

[0011] The preparation method of the magnetic nanocore comprises the following steps:

[0012] S1: weigh 27-54 g FeCl 3 6H 2 O, FeCl according to the mass volume ratio of 2.7-5.4 g: 100 mL 3 6H 2 O is dissolved in deionized water to obtain FeCl 3 Solution;

[0013] S2: weigh 20-40 g FeSO 4 7H 2 O, added to the FeCl obtained in step S1 3 solution, stirring until completely dissolved to obtain an iron salt solution;

[0014] S3: Under nitrogen atmosphere, heat the iron salt solution obtained in step S2 to 70°C while stirring, weigh 50-100g 25% NH 4OH solution was added as a precipitant, and the pH was adjusted and maintained in the range of 10.0±0.2. Stirring was continued for 1 h at a stirring speed of 80 rpm to generate black Fe 3 O 4 precipitation;

[0015] S4: Use a magnetic separator to separate the Fe generated in step S3 3 O 4 The precipitate was separated from the solution, washed three times with deionized water and anhydrous ethanol respectively, and then dried in a vacuum drying oven at 60°C for 12 h to obtain the magnetic nanocore.

[0016] The present invention also provides a method for preparing a visible light photocatalytic composite material, which specifically comprises the following steps:

[0017] Step 1: Weigh 10-50 g of magnetic nanocores, disperse them in 40% (v / v) ethanol aqueous solution at a mass volume ratio of 1-5 g: 60 mL, and perform ultrasonic treatment at 120 W for 30 min to obtain a dispersion;

[0018] Step 2: Weigh 20-80 g TiO 2 The precursor and 20-80 g of stabilizer are mixed and stirred evenly, and then slowly added to the dispersion obtained in step 1 to obtain Fe 3 O 4 @TiO 2 Reaction solution;

[0019] Step 3: Weigh 40-100 g gC 3 N 4 The precursor is added to the Fe obtained in step 2 3 O 4 @TiO 2 The reaction solution was stirred evenly to obtain a primary mixed solution, which was transferred to a high-pressure reactor and reacted at 40 MPa and 180°C for 6 h. After the reaction was completed, it was cooled to room temperature and a precipitate appeared. The precipitate was collected by a magnetic separator and washed with deionized water and anhydrous ethanol three times in sequence, and dried in an oven at 60°C for 12 h to obtain dry particles. The dry particles were calcined in a tubular furnace at a heating rate of 5°C / min and kept at 550°C for 2 h to obtain Fe 3 O 4 @TiO 2 / gC 3 N 4 ;

[0020] Step 4: Add the Fe obtained in step 3 to the 3 O 4 @TiO 2 / gC3 N 4 Soak in H 2 SO 4 -H 2 O 2 The mixed solution (volume ratio 1:1) was added for 20 min, and a precipitate appeared. The precipitate was filtered, washed with deionized water, and dried to obtain hydroxylated Fe 3 O 4 @TiO 2 / gC 3 N 4 ;

[0021] Step 5: Hydroxylated Fe obtained in step 4 3 O 4 @TiO 2 / gC 3 N 4 Dispersed in a dispersant, weigh 50-200 g of the modifier and add it to the reaction, transfer the precipitate and wash it with deionized water or anhydrous ethanol and dry it to obtain the modified Fe 3 O 4 @TiO 2 / gC 3 N 4 , that is, visible light photocatalytic composite materials.

[0022] Furthermore, the modifier is selected from any one of MPTS (3-mercaptopropyltriethoxysilane), ethylenediamine, chlorosulfonic acid and EDTA-2Na (disodium ethylenediaminetetraacetate).

[0023] Furthermore, the dispersant is selected from any one of deionized water, anhydrous ethanol, dichloromethane and an ethanol-citric acid mixed solution (volume ratio 1:1).

[0024] The beneficial effects achieved by the present invention are as follows:

[0025] The visible light photocatalytic composite material prepared by the present invention is a gC 3 N 4 With TiO 2 Composite, constructed a photocatalytic material with heterojunction, gC 3 N 4 It provides a narrow bandgap structure to enhance the utilization of visible light. It can absorb visible light to generate photogenerated electrons and holes under illumination. The photogenerated electrons are transferred to TiO through the heterojunction. 2 The interface forms superoxide free radicals with oxygen molecules in the environment or hydroxyl free radicals with water molecules / hydroxyl groups, attacking and degrading organic pollutants into non-toxic small molecules, achieving environmental governance. 2The high surface activity of the photocatalytic material further improves the photocatalytic reaction rate, avoids the rapid recombination of electrons and holes, and further improves the efficiency of the redox reaction; the two significantly improve the ability of photocatalytic degradation of organic pollutants through interfacial synergy. At the same time, after the action of the modifier, thiol, amino, carboxyl and sulfonic acid groups can be introduced on the surface of the material, which can specifically adsorb or chelate Hg 2+ 、Cd 2+ , Pb 2+ Cr 3+ and Zn 2+ It can simultaneously remove heavy metal ions in water and demonstrate excellent dual-functional treatment performance; the adsorbed heavy metal ions can be further converted into low-toxic or stable states by reacting with oxidative intermediates generated in the photocatalytic process, thereby achieving deep removal; in addition, the adsorption process reduces the concentration of heavy metal ions in the solution, weakens its inhibitory effect on the photocatalytic process, improves the photocatalytic efficiency, and realizes the integrated treatment of multiple pollutants.

[0026] Compared with the prior art, the material of the present invention has both recyclability and multifunctionality, and solves the problem that traditional photocatalytic materials are difficult to deal with organic matter and heavy metal pollution at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The modified Fe prepared in Example 1 and Example 5-7 3 O 4 @TiO 2 / gC 3 N 4 The photocatalytic performance test results;

[0028] Figure 2 The modified Fe prepared in Example 1-4 3 O 4 @TiO 2 / gC 3 N 4 Fourier transform infrared spectroscopy analysis results;

[0029] Figure 3 The modified Fe prepared in Example 1-4 3 O 4 @TiO 2 / gC 3 N 4 X-ray diffraction test results;

[0030] Figure 4 The modified Fe prepared in Example 1 and Example 5-7 3 O 4 @TiO 2 / gC 3 N4 UV-Vis diffuse reflectance spectroscopy test results;

[0031] Figure 5 The modified Fe prepared in Example 1-4 3 O 4 @TiO 2 / gC 3 N 4 Test results of heavy metal ion adsorption capacity;

[0032] Figure 6 The thiolated Fe prepared in Example 1 3 O 4 @TiO 2 / gC 3 N 4 Results of the photocatalytic performance investigation after recycling.

[0033] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0035] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0036] In the following examples, unless otherwise specified, conventional methods are used; the materials used in the following examples, unless otherwise specified, are all new materials purchased from the market.

[0037] Example 1: This example provides a visible light photocatalytic composite material, which includes the following raw materials by weight: 30 g of magnetic nanocore, Ti(OBu) 4 50 g, acetic acid 50 g, urea 80 g and MPTS 120 g.

[0038] The magnetic nanocore comprises the following raw materials by weight: FeCl 3 6H 2 O 40 g, FeSO4 7H 2 O 30 g and 25% NH 4 OH solution 80 g, the specific preparation method is as follows:

[0039] S1: weigh 40 g FeCl 3 6H 2 O, FeCl 3 6H 2 O is dissolved in deionized water to obtain FeCl 3 Solution;

[0040] S2: Weigh 30 gFeSO 4 7H 2 O, added to the FeCl obtained in step S1 3 solution, stirring until completely dissolved to obtain an iron salt solution;

[0041] S3: Under nitrogen atmosphere, heat the iron salt solution obtained in step S2 to 70°C while stirring, weigh 80 g 25% NH 4 OH solution was added as a precipitant, the pH was adjusted and maintained at 10.0, and stirring was continued for 1 h at a stirring speed of 80 rpm to generate black Fe 3 O 4 precipitation;

[0042] S4: Use a magnetic separator to separate the Fe generated in step S3 3 O 4 The precipitate was separated from the solution, washed three times with deionized water and anhydrous ethanol respectively, and then dried in a vacuum drying oven at 60°C for 12 h to obtain the magnetic nanocore.

[0043] This embodiment also provides a method for preparing a visible light photocatalytic composite material, which specifically comprises the following steps:

[0044] Step 1: Weigh 30 g of magnetic nanocores, disperse them in 40% ethanol aqueous solution at a mass volume ratio of 3 g:60 mL, and perform ultrasonic treatment at 120 W for 30 min to obtain a dispersion;

[0045] Step 2: Weigh 50 g Ti(OBu) 4 Mix with 50 g acetic acid, stir evenly, and slowly add to the dispersion obtained in step 1 to obtain Fe 3 O 4 @TiO 2 Reaction solution;

[0046] Step 3: Weigh 80 g of urea and add it to the Fe 3 O4 @TiO 2 The reaction solution was stirred evenly to obtain a primary mixed solution, which was transferred to a high-pressure reactor and reacted at 40 MPa and 180°C for 6 h. After the reaction was completed, it was cooled to room temperature and a precipitate appeared. The precipitate was collected by a magnetic separator and washed with deionized water and anhydrous ethanol three times in sequence, and dried in an oven at 60°C for 12 h to obtain dry particles. The dry particles were calcined in a tubular furnace at a heating rate of 5°C / min and kept at 550°C for 2 h to obtain Fe 3 O 4 @TiO 2 / gC 3 N 4 ;

[0047] Step 4: Add the Fe obtained in step 3 to the 3 O 4 @TiO 2 / gC 3 N 4 Soak in H 2 SO 4 -H 2 O 2 After 20 min in the mixed solution, a precipitate appeared. The precipitate was filtered, washed with deionized water, and dried to obtain hydroxylated Fe 3 O 4 @TiO 2 / gC 3 N 4 ;

[0048] Step 5: Hydroxylate Fe 3 O 4 @TiO 2 / gC 3 N 4 Dispersed in anhydrous ethanol at a mass volume ratio of 1 g:10 mL, 0.5 mL of acetic acid as a catalyst and 120 g of MPTS were added thereto, reacted at room temperature for 4 h, the precipitate was transferred and washed with anhydrous ethanol and dried to obtain thiolated Fe 3 O 4 @TiO 2 / gC 3 N 4 , that is, visible light photocatalytic composite materials.

[0049] Example 2: This example provides a visible light photocatalytic composite material, which includes the following raw materials by weight: 50 g of magnetic nanocore, Ti(OBu) 4 20 g, acetic acid 20 g, urea 40 g and ethylenediamine 50 g.

[0050] The magnetic nanocore comprises the following raw materials by weight: FeCl 3 6H 2 O 27 g, FeSO 4 7H 2 O 20 g and 25% NH 4 OH solution 50 g, the specific preparation method is as follows:

[0051] S1: weigh 27 g FeCl 3 6H 2 O, FeCl 3 6H 2 O is dissolved in deionized water to obtain FeCl 3 Solution;

[0052] S2: Weigh 20 gFeSO 4 7H 2 O, added to the FeCl obtained in step S1 3 solution, stirring until completely dissolved to obtain an iron salt solution;

[0053] S3: Under nitrogen atmosphere, heat the iron salt solution obtained in step S2 to 70°C while stirring, weigh 50 g 25% NH 4 OH solution was added as a precipitant, the pH was adjusted and maintained at 10.0, and stirring was continued for 1 h at a stirring speed of 80 rpm to generate black Fe 3 O 4 precipitation;

[0054] S4: Use a magnetic separator to separate the Fe generated in step S3 3 O 4 The precipitate was separated from the solution, washed three times with deionized water and anhydrous ethanol respectively, and then dried in a vacuum drying oven at 60°C for 12 h to obtain the magnetic nanocore.

[0055] This embodiment also provides a method for preparing a visible light photocatalytic composite material, which specifically comprises the following steps:

[0056] Step 1: Weigh 50 g of magnetic nanocores, disperse them in 40% ethanol aqueous solution at a mass volume ratio of 5 g:60 mL, and perform ultrasonic treatment at 120 W for 30 min to obtain a dispersion;

[0057] Step 2: Weigh 20 g Ti(OBu) 4 Mix with 20 g of acetic acid, stir evenly, and slowly add to the dispersion obtained in step 1 to obtain Fe 3 O 4 @TiO 2Reaction solution;

[0058] Step 3: Weigh 40 g of urea and add it to the Fe 3 O 4 @TiO 2 The reaction solution was stirred evenly to obtain a primary mixed solution, which was transferred to a high-pressure reactor and reacted at 40 MPa and 180°C for 6 h. After the reaction was completed, it was cooled to room temperature and a precipitate appeared. The precipitate was collected by a magnetic separator and washed with deionized water and anhydrous ethanol three times in sequence, and dried in an oven at 60°C for 12 h to obtain dry particles. The dry particles were calcined in a tubular furnace at a heating rate of 5°C / min and kept at 550°C for 2 h to obtain Fe 3 O 4 @TiO 2 / gC 3 N 4 ;

[0059] Step 4: Add the Fe obtained in step 3 to the 3 O 4 @TiO 2 / gC 3 N 4 Soak in H 2 SO 4 -H 2 O 2 After 20 min in the mixed solution, a precipitate appeared. The precipitate was filtered, washed with deionized water, and dried to obtain hydroxylated Fe 3 O 4 @TiO 2 / gC 3 N 4 ;

[0060] Step 5: Hydroxylated Fe 3 O 4 @TiO 2 / gC 3 N 4 Soak in a mixed solution of ethanol and citric acid (volume ratio 1:1) for 2 h, transfer the precipitate, wash it with deionized water, and dry it to obtain carboxylated Fe 3 O 4 @TiO 2 / gC 3 N 4 50 g of ethylenediamine was weighed and dissolved in deionized water to prepare a 6 mg / mL ethylenediamine solution. The carboxylated Fe 3 O 4 @TiO 2 / gC3 N 4 The activator was transferred to an activator, which was prepared from EDC (1-ethyl-(3-dimethylaminopropyl) carbodiimide), NHS (N-hydroxysuccinimide) and MES buffer solution at pH 6.0, wherein the concentrations of EDC and NHS were 3.8 mg / mL and 2.8 mg / mL, respectively. After stirring and activating for 30 min, an ethylenediamine solution of equal volume to the activator was added, and stirring was continued at 30°C for 40 min for amidation reaction. After the reaction was completed, the precipitate was transferred and washed with deionized water and dried to obtain amino Fe 3 O 4 @TiO 2 / gC 3 N 4 , that is, visible light photocatalytic composite materials.

[0061] Example 3: This example provides a visible light photocatalytic composite material, which includes the following raw materials by weight: 10 g of magnetic nanocore, Ti(OBu) 4 80 g, acetic acid 80 g, urea 100 g and chlorosulfonic acid 200 g.

[0062] The magnetic nanocore comprises the following raw materials by weight: FeCl 3 6H 2 O 54 g, FeSO 4 7H 2 O 40 g and 25% NH 4 OH solution 100 g, the specific preparation method is as follows:

[0063] S1: weigh 54 g FeCl 3 6H 2 O, FeCl 3 6H 2 O is dissolved in deionized water to obtain FeCl 3 Solution;

[0064] S2: Weigh 40 gFeSO 4 7H 2 O, added to the FeCl obtained in step S1 3 solution, stirring until completely dissolved to obtain an iron salt solution;

[0065] S3: Under nitrogen atmosphere, heat the iron salt solution obtained in step S2 to 70°C while stirring, weigh 100 g 25% NH 4 OH solution was added as a precipitant, the pH was adjusted and maintained at 10.0, and stirring was continued for 1 h at a stirring speed of 80 rpm to generate black Fe3 O 4 precipitation;

[0066] S4: Use a magnetic separator to separate the Fe generated in step S3 3 O 4 The precipitate was separated from the solution, washed three times with deionized water and anhydrous ethanol respectively, and then dried in a vacuum drying oven at 60°C for 12 h to obtain the magnetic nanocore.

[0067] This embodiment also provides a method for preparing a visible light photocatalytic composite material, which specifically comprises the following steps:

[0068] Step 1: Weigh 10 g of magnetic nanocores, disperse them in 40% ethanol aqueous solution at a mass volume ratio of 1 g:60 mL, and perform ultrasonic treatment at 120 W for 30 min to obtain a dispersion;

[0069] Step 2: Weigh 80 g Ti(OBu) 4 Mix with 80 g of acetic acid, stir evenly, and slowly add to the dispersion obtained in step 1 to obtain Fe 3 O 4 @TiO 2 Reaction solution;

[0070] Step 3: Weigh 100 g of urea and add it to the Fe 3 O 4 @TiO 2 The reaction solution was stirred evenly to obtain a primary mixed solution, which was transferred to a high-pressure reactor and reacted at 40 MPa and 180°C for 6 h. After the reaction was completed, it was cooled to room temperature and a precipitate appeared. The precipitate was collected by a magnetic separator and washed with deionized water and anhydrous ethanol three times in sequence, and dried in an oven at 60°C for 12 h to obtain dry particles. The dry particles were calcined in a tubular furnace at a heating rate of 5°C / min and kept at 550°C for 2 h to obtain Fe 3 O 4 @TiO 2 / gC 3 N 4 ;

[0071] Step 4: Add the Fe obtained in step 3 to the 3 O 4 @TiO 2 / gC 3 N 4 Soak in H 2 SO 4 -H 2 O 2After 20 min in the mixed solution, a precipitate appeared. The precipitate was filtered, washed with deionized water, and dried to obtain hydroxylated Fe 3 O 4 @TiO 2 / gC 3 N 4 ;

[0072] Step 5: Hydroxylated Fe 3 O 4 @TiO 2 / gC 3 N 4 The suspension was dispersed in dichloromethane and ultrasonically dispersed at 100 W for 10 min to obtain a suspension. 200 g of chlorosulfonic acid was slowly added dropwise while stirring under ice bath conditions. After the addition was completed, the reaction mixture was stirred and reacted for 2 h. After completion, the reaction solution was transferred to ice water to neutralize the generated HCl. The precipitate was transferred and washed with deionized water and dried to obtain sulfonated Fe 3 O 4 @TiO 2 / gC 3 N 4 , that is, visible light photocatalytic composite materials.

[0073] Example 4: This example provides a visible light photocatalytic composite material, which includes the following raw materials by weight: 30 g of magnetic nanocore, Ti(OBu) 4 50 g, acetic acid 50 g, urea 80 g and EDTA-2Na 140 g.

[0074] The magnetic nanocore comprises the following raw materials by weight: FeCl 3 6H 2 O 40 g, FeSO 4 7H 2 O 30 g and 25% NH 4 OH solution 80 g, the specific preparation method is as follows:

[0075] S1: weigh 40 g FeCl 3 6H 2 O, FeCl 3 6H 2 O is dissolved in deionized water to obtain FeCl 3 Solution;

[0076] S2: Weigh 30 gFeSO 4 7H 2 O, added to the FeCl obtained in step S1 3solution, stirring until completely dissolved to obtain an iron salt solution;

[0077] S3: Under nitrogen atmosphere, heat the iron salt solution obtained in step S2 to 70°C while stirring, weigh 80 g 25% NH 4 OH solution was added as a precipitant, the pH was adjusted and maintained at 10.0, and stirring was continued for 1 h at a stirring speed of 80 rpm to generate black Fe 3 O 4 precipitation;

[0078] S4: Use a magnetic separator to separate the Fe generated in step S3 3 O 4 The precipitate was separated from the solution, washed three times with deionized water and anhydrous ethanol respectively, and then dried in a vacuum drying oven at 60°C for 12 h to obtain the magnetic nanocore.

[0079] This embodiment also provides a method for preparing a visible light photocatalytic composite material, which specifically comprises the following steps:

[0080] Step 1: Weigh 30 g of magnetic nanocores, disperse them in 40% ethanol aqueous solution at a mass volume ratio of 3 g:60 mL, and perform ultrasonic treatment at 120 W for 30 min to obtain a dispersion;

[0081] Step 2: Weigh 50 g Ti(OBu) 4 Mix with 50 g acetic acid, stir evenly, and slowly add to the dispersion obtained in step 1 to obtain Fe 3 O 4 @TiO 2 Reaction solution;

[0082] Step 3: Weigh 80 g of urea and add it to the Fe 3 O 4 @TiO 2 The reaction solution was stirred evenly to obtain a primary mixed solution, which was transferred to a high-pressure reactor and reacted at 40 MPa and 180°C for 6 h. After the reaction was completed, it was cooled to room temperature and a precipitate appeared. The precipitate was collected by a magnetic separator and washed with deionized water and anhydrous ethanol three times in sequence, and dried in an oven at 60°C for 12 h to obtain dry particles. The dry particles were calcined in a tubular furnace at a heating rate of 5°C / min and kept at 550°C for 2 h to obtain Fe 3 O 4 @TiO 2 / gC 3 N 4 ;

[0083] Step 4: Add the Fe obtained in step 3 to the3 O 4 @TiO 2 / gC 3 N 4 Soak in H 2 SO 4 -H 2 O 2 After 20 min in the mixed solution, a precipitate appeared. The precipitate was filtered, washed with deionized water, and dried to obtain hydroxylated Fe 3 O 4 @TiO 2 / gC 3 N 4 ;

[0084] Step 5: Weigh 140 g of EDTA-2Na and dissolve it in deionized water to prepare a 20 mg / mL EDTA-2Na solution. Add hydroxylated Fe 3 O 4 @TiO 2 / gC 3 N 4 Disperse in deionized water, add an equal volume of EDTA-2Na solution, heat to 50 °C, stir, react for 4 h, transfer the precipitate, wash with anhydrous ethanol, and dry to obtain EDTA Fe 3 O 4 @TiO 2 / gC 3 N 4 , that is, visible light photocatalytic composite materials.

[0085] Example 5: This example provides a visible light photocatalytic composite material, which includes the following raw materials by weight: 30 g of magnetic nanocore, Ti(OiPr) 4 50 g, acetylacetone 50 g, thiourea 80 g and MPTS 120 g.

[0086] The magnetic nanocore comprises the following raw materials by weight: FeCl 3 6H 2 O 40 g, FeSO 4 7H 2 O 30 g and 25% NH 4 OH solution 80 g, the specific preparation method is as follows:

[0087] S1: weigh 40 g FeCl 3 6H 2 O, FeCl 3 6H 2O is dissolved in deionized water to obtain FeCl 3 Solution;

[0088] S2: Weigh 30 gFeSO 4 7H 2 O, added to the FeCl obtained in step S1 3 solution, stirring until completely dissolved to obtain an iron salt solution;

[0089] S3: Under nitrogen atmosphere, heat the iron salt solution obtained in step S2 to 70°C while stirring, weigh 80 g 25% NH 4 OH solution was added as a precipitant, the pH was adjusted and maintained at 10.0, and stirring was continued for 1 h at a stirring speed of 80 rpm to generate black Fe 3 O 4 precipitation;

[0090] S4: Use a magnetic separator to separate the Fe generated in step S3 3 O 4 The precipitate was separated from the solution, washed three times with deionized water and anhydrous ethanol respectively, and then dried in a vacuum drying oven at 60°C for 12 h to obtain the magnetic nanocore.

[0091] This embodiment also provides a method for preparing a visible light photocatalytic composite material, which specifically comprises the following steps:

[0092] Step 1: Weigh 30 g of magnetic nanocores, disperse them in 40% ethanol aqueous solution at a mass volume ratio of 3 g:60 mL, and perform ultrasonic treatment at 120 W for 30 min to obtain a dispersion;

[0093] Step 2: Weigh 50 g Ti(OiPr) 4 Mix with 50 g of acetylacetone, stir evenly, and slowly add to the dispersion obtained in step 1 to obtain Fe 3 O 4 @TiO 2 Reaction solution;

[0094] Step 3: Weigh 80 g of thiourea and add it to the Fe 3 O 4 @TiO 2 The reaction solution was stirred evenly to obtain a primary mixed solution, which was transferred to a high-pressure reactor and reacted at 40 MPa and 180°C for 6 h. After the reaction was completed, it was cooled to room temperature and a precipitate appeared. The precipitate was collected by a magnetic separator and washed with deionized water and anhydrous ethanol three times in sequence, and dried in an oven at 60°C for 12 h to obtain dry particles. The dry particles were calcined in a tubular furnace at a heating rate of 5°C / min and kept at 550°C for 2 h to obtain Fe3 O 4 @TiO 2 / gC 3 N 4 ;

[0095] Step 4: Add the Fe obtained in step 3 to the 3 O 4 @TiO 2 / gC 3 N 4 Soak in H 2 SO 4 -H 2 O 2 After 20 min in the mixed solution, a precipitate appeared. The precipitate was filtered, washed with deionized water, and dried to obtain hydroxylated Fe 3 O 4 @TiO 2 / gC 3 N 4 ;

[0096] Step 5: Hydroxylate Fe 3 O 4 @TiO 2 / gC 3 N 4 Dispersed in anhydrous ethanol at a mass volume ratio of 1 g:10 mL, 120 g of MPTS and 0.5 mL of acetic acid were weighed as catalysts, reacted at room temperature for 4 h, and the precipitate was transferred and washed with anhydrous ethanol and dried to obtain thiolated Fe 3 O 4 @TiO 2 / gC 3 N 4 , that is, visible light photocatalytic composite materials.

[0097] Example 6: This example provides a visible light photocatalytic composite material, which includes the following raw materials by weight: 30 g of magnetic nanocore, LiTiO 3 50 g, ethyl acetate 50 g, dicyandiamide 80 g and MPTS 120 g.

[0098] The magnetic nanocore comprises the following raw materials by weight: FeCl 3 6H 2 O 40 g, FeSO 4 7H 2 O 30 g and 25% NH 4 OH solution 80 g, the specific preparation method is as follows:

[0099] S1: weigh 40 g FeCl3 6H 2 O, FeCl 3 6H 2 O is dissolved in deionized water to obtain FeCl 3 Solution;

[0100] S2: Weigh 30 gFeSO 4 7H 2 O, added to the FeCl obtained in step S1 3 solution, stirring until completely dissolved to obtain an iron salt solution;

[0101] S3: Under nitrogen atmosphere, heat the iron salt solution obtained in step S2 to 70°C while stirring, weigh 80 g 25% NH 4 OH solution was added as a precipitant, the pH was adjusted and maintained at 10.0, and stirring was continued for 1 h at a stirring speed of 80 rpm to generate black Fe 3 O 4 precipitation;

[0102] S4: Use a magnetic separator to separate the Fe generated in step S3 3 O 4 The precipitate was separated from the solution, washed three times with deionized water and anhydrous ethanol respectively, and then dried in a vacuum drying oven at 60°C for 12 h to obtain the magnetic nanocore.

[0103] This embodiment also provides a method for preparing a visible light photocatalytic composite material, which specifically comprises the following steps:

[0104] Step 1: Weigh 30 g of magnetic nanocores, disperse them in 40% ethanol aqueous solution at a mass volume ratio of 3 g:60 mL, and perform ultrasonic treatment at 120 W for 30 min to obtain a dispersion;

[0105] Step 2: Weigh 50 g LiTiO 3 and 50 g of ethyl acetate, stirred evenly, and slowly added to the dispersion obtained in step 1 to obtain Fe 3 O 4 @TiO 2 Reaction solution;

[0106] Step 3: Weigh 80 g of dicyandiamide and add it to the Fe 3 O 4 @TiO 2The reaction solution was stirred evenly to obtain a primary mixed solution, which was transferred to a high-pressure reactor and reacted at 40 MPa and 180°C for 6 h. After the reaction was completed, it was cooled to room temperature and a precipitate appeared. The precipitate was collected by a magnetic separator and washed with deionized water and anhydrous ethanol three times in sequence, and dried in an oven at 60°C for 12 h to obtain dry particles. The dry particles were calcined in a tubular furnace at a heating rate of 5°C / min and kept at 550°C for 2 h to obtain Fe 3 O 4 @TiO 2 / gC 3 N 4 ;

[0107] Step 4: Add the Fe obtained in step 3 to the 3 O 4 @TiO 2 / gC 3 N 4 Soak in H 2 SO 4 -H 2 O 2 After 20 min in the mixed solution, a precipitate appeared. The precipitate was filtered, washed with deionized water, and dried to obtain hydroxylated Fe 3 O 4 @TiO 2 / gC 3 N 4 ;

[0108] Step 5: Hydroxylate Fe 3 O 4 @TiO 2 / gC 3 N 4 Dispersed in anhydrous ethanol at a mass volume ratio of 1 g:10 mL, 120 g of MPTS and 0.5 mL of acetic acid were weighed as catalysts, reacted at room temperature for 4 h, and the precipitate was transferred and washed with anhydrous ethanol and dried to obtain thiolated Fe 3 O 4 @TiO 2 / gC 3 N 4 , that is, visible light photocatalytic composite materials.

[0109] Example 7: This example provides a visible light photocatalytic composite material, which includes the following raw materials by weight: 30 g of magnetic nanocore, Ti(OBu) 4 50 g, triethanolamine 50 g, citrulline 80 g and MPTS 120 g.

[0110] The magnetic nanocore comprises the following raw materials by weight: FeCl 3 6H 2 O 40 g, FeSO 4 7H 2 O 30 g and 25% NH 4 OH solution 80 g, the specific preparation method is as follows:

[0111] S1: weigh 40 g FeCl 3 6H 2 O, FeCl 3 6H 2 O is dissolved in deionized water to obtain FeCl 3 Solution;

[0112] S2: weigh 30gFeSO 4 7H 2 O, added to the FeCl obtained in step S1 3 solution, stirring until completely dissolved to obtain an iron salt solution;

[0113] S3: Under nitrogen atmosphere, heat the iron salt solution obtained in step S2 to 70°C while stirring, weigh 80 g 25% NH 4 OH solution was added as a precipitant, the pH was adjusted and maintained at 10.0, and stirring was continued for 1 h at a stirring speed of 80 rpm to generate black Fe 3 O 4 precipitation;

[0114] S4: Use a magnetic separator to separate the Fe generated in step S3 3 O 4 The precipitate was separated from the solution, washed three times with deionized water and anhydrous ethanol respectively, and then dried in a vacuum drying oven at 60°C for 12 h to obtain the magnetic nanocore.

[0115] This embodiment also provides a method for preparing a visible light photocatalytic composite material, which specifically comprises the following steps:

[0116] Step 1: Weigh 30 g of magnetic nanocores, disperse them in 40% ethanol aqueous solution at a mass volume ratio of 3 g:60 mL, and perform ultrasonic treatment at 120 W for 30 min to obtain a dispersion;

[0117] Step 2: Weigh 50 g Ti(OBu) 4 and 50 g of triethanolamine, stirred evenly, and slowly added to the dispersion obtained in step 1 to obtain Fe 3 O 4 @TiO 2 Reaction solution;

[0118] Step 3: Weigh 80 g of citrulline and add it to the Fe 3 O 4 @TiO 2 The reaction solution was stirred evenly to obtain a primary mixed solution, which was transferred to a high-pressure reactor and reacted at 40 MPa and 180°C for 6 h. After the reaction was completed, it was cooled to room temperature and a precipitate appeared. The precipitate was collected by a magnetic separator and washed with deionized water and anhydrous ethanol three times in sequence, and dried in an oven at 60°C for 12 h to obtain dry particles. The dry particles were calcined in a tubular furnace at a heating rate of 5°C / min and kept at 550°C for 2 h to obtain Fe 3 O 4 @TiO 2 / gC 3 N 4 ;

[0119] Step 4: Add the Fe obtained in step 3 to the 3 O 4 @TiO 2 / gC 3 N 4 Soak in H 2 SO 4 -H 2 O 2 After 20 min in the mixed solution, a precipitate appeared. The precipitate was filtered, washed with deionized water, and dried to obtain hydroxylated Fe 3 O 4 @TiO 2 / gC 3 N 4 ;

[0120] Step 5: Hydroxylate Fe 3 O 4 @TiO 2 / gC 3 N 4 Dispersed in anhydrous ethanol at a mass volume ratio of 1 g:10 mL, 120 g of MPTS and 0.5 mL of acetic acid were weighed as catalysts, reacted at room temperature for 4 h, and the precipitate was transferred and washed with anhydrous ethanol and dried to obtain thiolated Fe 3 O 4 @TiO 2 / gC 3 N 4 , that is, visible light photocatalytic composite materials.

[0121] Photocatalytic performance test

[0122] Weigh the Fe modified by the modifier prepared in Example 1 and Example 5-73 O 4 @TiO 2 / gC 3 N 4 50 mg of each was placed in a beaker, and 100 mL of methyl orange solution (10 mg / mL) was added. After being protected from light and ultrasonicated at 120 W for 5 min, the mixture was transferred to a photochemical reactor and stirred for 30 min in a dark place. The light source was turned on, and 4 mL of the solution was taken at 5, 10, 20, 30, 40, 50, and 60 min. After being sieved through a molecular sieve, the absorbance of the solution was measured at a wavelength of 463 nm (A), and the photocatalytic degradation rate was calculated according to the following formula: C% = (A 0 -A t ) / A 0 ×100%,A 0 A is the absorbance of the solution before turning on the light source. t is the absorbance value of the solution detected at different time points, the results are shown in Figure 1 .

[0123] FT-IR (Fourier Transform Infrared Spectroscopy) Analysis

[0124] Take the Fe modified by the modifier prepared in Example 1-4 3 O 4 @TiO 2 / gC 3 N 4 FT-IR analysis was performed using the KBr pellet method. The results are shown in Figure 2 .

[0125] XRD (X-ray diffraction) analysis

[0126] The Fe modified by the modifier prepared in Examples 1-4 was analyzed by X-ray diffractometer. 3 O 4 @TiO 2 / gC 3 N 4 Composition and crystal structure of the samples, Cu K α The working current and voltage were 40 mA and 40 kV respectively. The results are shown in Figure 3 .

[0127] Light absorption characteristics investigation

[0128] Take the Fe modified by the modifier prepared in Example 1 and Example 5-7 3 O 4 @TiO 2 / gC 3 N 4 UV-Vis DRS (ultraviolet-visible diffuse reflectance spectroscopy) characterization analysis was performed, and the results are shown in Figure 4 .

[0129] Investigation on the adsorption performance of heavy metal ions

[0130] Take 200 mg / L concentration of Pb 2+ 、Cd 2+ 、Ag + , Cu 2+ Cr 3+ 、Al 3+ 100 mL of heavy metal ion solution was added to the above solution, and 50 mg of Fe modified by the modifier prepared in Example 1-4 was added to each of the above solutions. 3 O 4 @TiO 2 / gC 3 N 4 The mixture was shaken at 25°C and 150 rpm for 24 h. The reaction solution was filtered with a 0.45 μm filter membrane and the mass concentration of heavy metal ions after filtration was determined by atomic absorption spectrometry. The adsorption capacity of heavy metal ions was determined. The results are shown in Table 1. Figure 5 .

[0131] Reuse performance tests

[0132] Weigh 50 mg of the thiolated Fe prepared in Example 1 3 O 4 @TiO 2 / gC 3 N 4 100 mL of methyl orange solution (10 mg / mL) was added, and the mixture was transferred to a photochemical reactor after 120 W ultrasound for 5 min in a dark place. The mixture was stirred for 30 min in a dark place, and the light source was turned on. After 60 min, the supernatant was taken to detect the absorbance of the solution. The thiolated Fe 3 O 4 @TiO 2 / gC 3 N 4 Take out and dry, repeat the above process 5 times, and investigate the reuse performance of visible light photocatalytic composite materials. Figure 6 .

[0133] Figure 1 The photocatalytic activity test results show that Example 1 and Examples 5-7 all have good photocatalytic performance, among which the thiolated Fe prepared in Example 1 3 O 4 @TiO 2 / gC 3 N 4 The photocatalytic ability is the strongest and the reaction is fast, with methyl orange degradation exceeding 90% within 60 minutes.

[0134] Figure 2The FT-IR analysis results show that the samples in Examples 1-4 all have a wavelength of 1200-1650 cm -1 The characteristic absorption peaks of CN and C=N appear at 3400 cm -1 The stretching vibration peak of the surface hydroxyl group (-OH) appears at 3 O 4 @TiO 2 / gC 3 N 4 The synthesis was successful, and the 700 cm -1 and 2500-2600 cm -1 The absorption peak of 3300-3500 cm in Example 2 indicates that the thiol modification is successful. -1 The double peaks at 1040-1180 cm -1 The symmetric and asymmetric stretching vibration peaks of the S=O bond are shown, 600-800 cm in Example 4. -1 Peak is COO - Bending vibration peaks of the group.

[0135] Figure 3 The XRD results correspond to the FT-IR analysis results. The surface modification groups do not change the crystal form of the composite material and still retain its efficient photocatalytic ability.

[0136] Figure 4 The UV-Vis DRS diffuse reflectance results show that the group-modified Fe prepared from different raw materials 3 O 4 @TiO 2 / gC 3 N 4 There are differences in the photocatalytic broad spectra of the two species. Their absorption band edges are in the range of 515-540 nm, and the visible light wavelength range that triggers photocatalysis is increased. They all have high photocatalytic performance.

[0137] Figure 5 The group-modified Fe prepared in Examples 1-4 3 O 4 @TiO 2 / gC 3 N 4 There is specific adsorption behavior for heavy metal ions, and thiolization is conducive to the adsorption of Pb 2+ 、Cd 2+ 、Ag + , amination is beneficial to the adsorption of Cu 2+ Cr 3+ , sulfonic acid groups on Pb 2+ Cr 3+ 、Al 3+The adsorption capacity is strong. EDTA has a broad-spectrum multi-dentate adsorption capacity due to its abundant amino and carboxyl groups.

[0138] Figure 6 The photocatalytic recycling performance test results of the methyl orange solution showed that the thiolated Fe prepared in Example 1 3 O 4 @TiO 2 / gC 3 N 4 It is reusable, and its photocatalytic degradation efficiency is still higher than 80% after being reused 5 times.

[0139] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0140] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A visible light photocatalytic composite material, characterized in that: The visible light photocatalytic composite material comprises the following raw materials by weight: 10-50 g of magnetic nanocore, 20-80 g of TiO2 precursor, 20-80 g of stabilizer, 40-100 g of g-C3N4 precursor and 50-200 g of modifier; The TiO2 precursor is Ti(OBu)4, the stabilizer is acetylacetone, the g-C3N4 precursor is urea, and the modifier is EDTA-2Na; The magnetic nanocore comprises the following raw materials by weight: 27-54 g of FeCl3·6H2O, 20-40 g of FeSO4·7H2O and 50-100 g of 25% NH4OH solution. The preparation method of the magnetic nanocore specifically comprises the following steps: S1: Weigh FeCl3·6H2O and dissolve it in deionized water to obtain FeCl3 solution; S2: Weigh FeSO4·7H2O and add it to FeCl3 solution, stirring and dissolving to obtain an iron salt solution; S3: After heating the iron salt solution, add 25% NH4OH solution to adjust the pH and react to obtain Fe3O4 precipitation; S4: separating the Fe3O4 precipitate, washing and drying it to obtain the magnetic nanocore; The preparation method of the visible light photocatalytic composite material specifically comprises the following steps: Step 1: weigh the magnetic nanocores to prepare a dispersion; Step 2: Weigh the TiO2 precursor and stabilizer and add them to the dispersion to obtain a Fe3O4@TiO2 reaction solution; Step 3: Weigh the g-C3N4 precursor and add it to the Fe3O4@TiO2 reaction solution for reaction, collect the precipitate and calcine it to obtain Fe3O4@TiO2 / g-C3N4; Step 4: Hydroxylating Fe3O4@TiO2 / g-C3N4 to obtain hydroxylated Fe3O4@TiO2 / g-C3N4; Step 5: Use a modifier to modify the hydroxylated Fe3O4@TiO2 / g-C3N4 to obtain a visible light photocatalytic composite material.

2. The visible light photocatalytic composite material according to claim 1, characterized in that: In step S1, the mass volume ratio of the FeCl3·6H2O and deionized water is 2.7-5.4 g:100 mL; In step S3, the heating and pH adjustment process is carried out under a nitrogen atmosphere, and the pH is adjusted to 10.0±0.

2.

3. The visible light photocatalytic composite material according to claim 1, characterized in that: In step 1, the dispersion is prepared by dispersing the magnetic nanocores in a 40% volume fraction ethanol aqueous solution; In step 3, the reaction process is carried out in a high-pressure reactor, the collection and precipitation process uses a magnetic separator, and the calcination process is carried out in a tubular furnace; In step 4, the hydroxylation process is as follows: Fe3O4@TiO2 / g-C3N4 is immersed in a H2SO4-H2O2 mixed solution, a precipitate appears, and the precipitate is filtered, washed with deionized water, and dried.

4. The visible light photocatalytic composite material according to claim 3, characterized in that: Step 5 specifically includes the following steps: preparing an EDTA-2Na aqueous solution, dispersing the hydroxylated Fe3O4@TiO2 / g-C3N4 in deionized water, adding an equal volume of EDTA-2Na solution thereto, heating and reacting, transferring the precipitate and washing and drying it with anhydrous ethanol to obtain EDTA-treated Fe3O4@TiO2 / g-C3N4, i.e., a visible light photocatalytic composite material.